RELATIONSHIP BETWEEN SELECTED UNIVERSITY CULTURES AND STUDENT RETENTION IN CHARTERED CHRISTIAN UNIVERSITIES IN KENYA - KIPTANUI, KITUR JOHN (KABARAK UNIVERSITY, 2020)
This study sought to address the problem of low student retention in Chartered Christian Universities in Kenya. University cultures make up the academic and social environment in any university and are therefore key to students‘ retention. The purpose of this study was to establish the relationship between selected university cultures and student retention in Chartered Christian Universities in Kenya. The following objectives guided the study; to establish relationship between religious cultures, instruction cultures, discipline cultures and study cost management cultures and student retention in Chartered Christian Universities in Kenya. The significant of the study was in policy review and formulation. The study was based on Students‘ Integration Theory by Tinto (1993) and Cultural Model of Educational Management by Bush (2011). The descriptive survey research design was adopted. The targeted population comprised of 604yearfour students, 12Academic Deans, 5 chaplains, 5 Finance Managers, and 5 Deans of students in Chartered Christian Universities located in Nairobi, Kiambu, Machakos and Kericho counties. Census method was used to sample the respondents. Questionnaire and interviews were used to collect data. The questionnaire was piloted at Tangaza University and tested for reliability using test retest method and was validated by experts. The outcome of the tests showed that the intraclass correlation value was >.9 for both tests and the test was significant (p<.05) hence the tool was reliable for data collection. The qualitative data was cleaned for errors, coded, assigned labels and grouped for related themes. Quantitative data was analysed using descriptive statistics such as means and percentages and reported in tables and figures. Data analysis was done using tools in SPSS version 22. Pearson Product Moment Correlations CoEfficient, Analysis of Variance and regression analysis were computed to establish relationships between selected university cultures and student retention. The Embedded Design for mixed methods was used to integrate and present the quantitative and qualitative data outcomes. It was found out that religious cultures were related to student retention (r=0.437; p=0.000). On objective two, instruction cultures were related to student retention (r=0.482; p=0.000). Objective three shows that discipline cultures were related to student retention (r=0.591; p=0.000) and objective four; the result showed study cost management cultures were related to student retention (r=0.647; p=0.000). From these findings, all the four null hypotheses were rejected, and the alternate hypotheses adopted, meaning there is statistically significant relationship between university cultures and student retention in chartered Christian universities in Kenya. The Study recommends that chartered Christian universities in Kenya should take advantage of their cultures and should come up with policies to strengthen the existing cultures as they come up with new ones. The study recommends further that the Ministry of Education should develop policies that could facilitate student retention and review the existing policies on student retention in institutions of higher learning in Kenya and beyond. In addition, studies are recommended in other Christian universities which did not start as theological colleges, other private universities and in public universities to establish the relationship between university cultures and student retention.
Keywords: Student retention; chartered Christian Universities; Religious Cultures; Instruction Cultures; Discipline Cultures; Cost Management Cultures